7.8k views
0 votes
He system shown has _____ solution(s). y = x + 1 2y - x = 6 no one infinite

User Mrueg
by
4.4k points

2 Answers

5 votes

Answer: One solution.

Explanation:

You can solve the system of equations by applying the substitution method, as following:

- Subsitute
y=x+1 into the second equation and solve for x, then:


2(x+1)-x=6\\2x+2-x=6\\x=4

- Substitute the value of x obtained into one of the original equations:


y=4+1\\y=5

Thefore the system have one solution.

User Chriswhite
by
5.3k points
2 votes

Answer:

The given system have one solution.

Explanation:

We have given a system of equations.

y = x + 1 eq(1)

2y - x = 6 eq(2)

We use the substitution method to solve this question.

Putting eq(1) into eq(2), we have

2(x+1)-x = 6

2x+2-x = 6

Adding like terms, we have

x+2 = 6

x = 6-2

x = 4

Putting the value of x in eq(1), we have

y = 4+1

y = 5

hence, the given system have one solution.

User Ong Ming Soon
by
4.6k points